2018
DOI: 10.1098/rsos.172137
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 1,8-naphthalimide-based probes with fluorescent switch triggered by flufenamic acid

Abstract: In this work, we report the synthesis of novel fluorescent molecules, based on 1,8-naphthalimide thio- and amino-derivatives, designed to display an OFF-ON and ON-OFF photoelectron transfer fluorescence switch upon interaction with a proton-donor drug. We have functionalized the new probes to allow easy formation of a covalent link to polymer matrices, for future applications as drug delivery sensors. We have investigated the fluorescent switch of the new probes using flufenamic acid (FA, pKa 3.65), a water in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 34 publications
2
19
0
Order By: Relevance
“…4 Over the past few decades, uorescence organic molecules have been used for selective recognition of a wide range of analytes. [5][6][7] Development of small molecules which are able to interact with carbohydrates requires special recognition moieties capable of strong binding under physiological conditions. Among various materials for saccharide detection, use of boronic acid and its derivatives has attracted a great deal of attention because of their strong interactions with sugars.…”
Section: Introductionmentioning
confidence: 99%
“…4 Over the past few decades, uorescence organic molecules have been used for selective recognition of a wide range of analytes. [5][6][7] Development of small molecules which are able to interact with carbohydrates requires special recognition moieties capable of strong binding under physiological conditions. Among various materials for saccharide detection, use of boronic acid and its derivatives has attracted a great deal of attention because of their strong interactions with sugars.…”
Section: Introductionmentioning
confidence: 99%
“…Such derivatives have been already employed as fluorescent MIP monomers [ 26 , 27 , 28 ]; for example, monomer 5 was employed by Rouhani et al to develop a MIP sensor for caffeine, which showed a quenching of its fluorescence upon binding to the template with a limit of detection of 6.3 μM [ 29 ]. These very fluorescent molecules have been also used as probes for the detection of acidic drugs, biomolecules [ 30 ], and anions [ 31 ]. We have identified a small set of naphtalimide monomers ( 2 – 6 ) and synthesised them by literature methods [ 32 , 33 , 34 , 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…To overcome this challenge and increase the effective dose of MA, we encapsulated MA into a micellar nanocarrier (MA-Mc) using the controlled self-assembly of PEG-PPS, which can form diverse nanocarrier morphologies to efficiently deliver hydrophobic and hydrophilic moieties to APCs ( 21 ). To track the intracellular release of MA from micelles following uptake by cells, we modified the PEG-PPS copolymer by attaching an acid sensitive fluorophore (ASF, λ ex = 395 nm, λ em = 505 nm) ( 29 ) to the terminal end of the PPS block (PEG-PPS-ASF; Figures S1 , S2A ). The ASF contains an aminoquinoline ring, and the protonation of the tertiary amine within the ring leads to 98% quenching of fluorescence (Figure S1 ) ( 30 ).…”
Section: Resultsmentioning
confidence: 99%
“…An acid-sensitive fluorophore (ASF, λ ex = 395 nm, λ em = 505 nm) derived from a 1,8-naphthalamide was synthesized as previously described ( 29 , 30 ). The fluorophore was then modified to introduce a -SH containing linker on the naphthalimide ring for conjugation to PEG-PPS ( 31 ) (Figure S1 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation